TINGKAT UNDERPRICING DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Alya Hafsah, Haki; Khairunnisa, Khairunnisa (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study examines the correlation between financial factors and non-financial factors' effect on the underpricing phenomenon in IPOs in Indonesia. With a quantitative approach, this research uses secondary data originating from the IPO prospectus. The research sample was 107 from a total population of 272 companies conducting an IPO from 2018 to 2022. Factor analysis and multiple regression analysis act as analysis methods. Factor analysis findings show that financial leverage, profitability, underwriter reputation, and auditor reputation are correlated factors that can determine the level of underpricing. Furthermore, multiple linear regression analysis found a significant effect on the auditor's reputation to underpricing, while financial leverage, profitability, and the underwriter's reputation do not significantly affect the underpricing level. For both company managers and investors, this study shows the implications of reputable auditors during IPO, which can reduce underpricing by companies and increase investor interest.